Aligning First Language (L1) Curricula with PISA Reading Proficiency Levels: A Comparative Analysis of Ireland and Türkiye - Ulutaş, Mustafa (International Electronic Journal of Elementary Education, 2026)
This study undertakes a comparative examination of the alignment between first language (L1) curricula in Ireland and Türkiye and the PISA 2022 reading proficiency framework. Adopting a qualitative research design grounded in document analysis, the study systematically maps reading-related learning outcomes from both national curricula onto the proficiency levels defined by PISA. Rather than relying on conventional grade-level comparisons, the analysis employs a proficiency-oriented perspective to evaluate the cognitive demands embedded in curricula and the progression of reading skills. The findings indicate that the Irish curricula consistently incorporates higher-level reading skills associated with PISA Levels 4 and 5, supported by a clearly structured and coherent progression that begins in the early years of primary education. In contrast, Türkiye’s 2015–2019 curricula primarily emphasize basic and intermediate reading proficiencies corresponding to PISA Levels 2 and 3, while advanced reading skills are addressed in a limited, inconsistent, and fragmented manner. However, the analysis of the 2024 Maarif Model Turkish Language Curriculum reveals a substantial structural shift. This new model demonstrates greater potential to align with PISA’s advanced reading requirements, including critical, reflective, and problem-solving reading, by embedding these competencies within a more comprehensive and developmentally organized framework. The study concludes that examining curricula through their structural alignment with international proficiency standards provides a robust foundation for interpreting cross-national performance differences and offers practical insights to inform curriculum development and reform.